Sintilimab combined with apatinib plus capecitabine in the treatment of unresectable hepatocellular carcinoma: A prospective, open-label, single-arm, phase II clinical study - Li, Dailong; Xu, Lu; Ji, Jinxing; Bao, Dan; Hu, Juan; Qian, Ying; Zhou, Yinjie; Chen, Zhuo; Li, Daojun; Li, Xiaopeng; Zhang, Xiaoling; Wang, Hao; et al. (Frontiers in Immunology, 2022)
Objective To evaluate the efficacy and safety of sintilimab combined with apatinib plus capecitabine in the treatment of unresectable hepatocellular carcinoma (HCC) to provide a more effective first-line treatment for patients with advanced HCC. Methods This open-label, prospective, phase II study included patients with unresectable HCC who did not receive systematic treatment. The patients were treated with sintilimab (200 mg, intravenous drip, once every 3 weeks) combined with apatinib (250 mg, oral administration, once a day) plus capecitabine (1000 mg/m2, twice a day; after 2 weeks of oral administration, the drug was stopped for 1 week; course of treatment, 3 weeks). The primary endpoint was the objective response rate (ORR). The secondary endpoints included disease control rate (DCR), progression-free survival (PFS), duration of response (DoR), overall survival (OS), and safety. Results Forty-seven patients (1 lost to follow-up) were enrolled in the study. As of March 1, 2022, the ORR and DCR were 50.0% (95% CI: 34.9–65.1%) and 91.3% (95% CI: 79.2–97.6%), respectively, after blind, independent imaging evaluation. The median follow-up time was 18.7 months (95% CI: 17.2–20.2 months). The median PFS was 9.0 months (95% CI: 7.1–10.9 months). The median DoR was 10.8 months (95% CI: 4.8–16.8 months). The median OS was not reached, and the 1-year OS rate was 71.7% (95% CI: 56.5–84.0%). Only 28.3% (13/46) of patients had grade 3/4 treatment-related adverse events. Conclusion Sintilimab combined with apatinib plus capecitabine has good safety and anti-tumor activity as a first-line treatment for unresectable HCC. This is worthy of further multi-center, prospective, randomized, large-sample clinical studies. Clinical Trial Registration https://ClinicalTrials.gov, identifier NCT04411706.